Training of Future Education Managers For Professional Activities - Poliakova, Iana Viktorovna (2021)
Large-scale changes in the social and economic spheres of Russian society revealed the demands for managers with non-standard thinking and a high cultural level. Specific and ambiguous processes in politic, economic and social spheres in different parts of the world have general trends reflecting the evolution of global civilization. In this context, educational systems received new functions aimed at moral growth and improvement of competencies. The highest demand in the field of education is for experienced teachers and administrators who are able to improve the system of education and upbringing, develop scenarios for managing the teaching and learning process, offer the personality-oriented trajectories for students, make an independent choice and fulfill corrective and diagnostic functions. The transformed socio-economic context led to positive changes in the field of professional education. One of the basic features of the modern educational systems is the training of highly qualified education managers. Such individual characteristics as the ability to continuous self-improvement, creativity, communication skills, entrepreneurial skills, the ability to analyze and foresee, etc. play an increasing role in the professional training. The most important place in the training of education managers is occupied by pedagogical technologies aimed at mastering the necessary competencies in economics, management, psychology and related disciplines. In the context of the innovative transformations of Russian education, the pressing need to integrate new management schemes into the practice of educational institutions and the problem of pedagogical training in the field of management becomes very urgent. Qualified management creates conditions for improving the educational environment, increasing the quality of educational services. The educational system should prepare young citizens capable of making a feasible contribution to the formation of the law-based state. Currently, it is necessary to optimize the activities of education managers responsible for the implementation of the state programs to improve and innovate the economy, science and education. The management culture of education managers is beginning to play a decisive role in the creation of a democratic society in the Russian Federation based on respect for individual rights and freedoms. The creation of the most favorable conditions for the integration of students into the educational and cultural environment is aimed at creating a high level of management culture of future education managers.